Comparison of clinical examination and ultrasonography in the diagnosis of acute appendicitis - Chhetri, PK; Tayal, A; Deka, PK (Journal of College of Medical Sciences-Nepal, 2012)
This study was undertaken to compare clinical examination and ultrasonography (USG) in the diagnosis of acute appendicitis and to establish their accuracy in the diagnosis of acute appendicitis. 100 patients who presented to the emergency department with a clinical diagnosis of acute appendicitis were subjected to USG. After USG a specific diagnosis was made. Patients underwent appendicectomy on the basis of the surgeon‘s final clinical impression after correlating with USG findings. Histopathological examination of the appendicectomy specimen was taken as the gold standard for the diagnosis of acute appendicitis. Appendicectomy was performed in 74 patients. Out of these 74 cases, only 66 had appendicitis on histopathological examination. Eight normal appendixes were removed. Twenty-six patients were prevented from surgery after USG had shown an alternative diagnosis for the cause of pain in right iliac fossa. Clinical examination thus had a sensitivity and Positive Predictive Value (PPV) of 66%. USG examination made a preoperative diagnosis of acute appendicitis in 62 of the 66 patients. However the remaining 4 cases with appendicitis were missed by USG. USG had a sensitivity of 93.93%, specificity of 100%, PPV of 100%, NPV of 89.47% and an overall accuracy of 96% in the diagnosis of acute appendicitis. USG is thus a sensitive and specific imaging modality in the diagnostic work up of patients with right iliac fossa pain. USG may improve the diagnostic accuracy in patients with suspected acute appendicitis. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 34-40 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6678